Modification of the ZnO acoustic phonon dispersion with temperature: inelastic neutron scattering data - Gas, K.; Łusakowska, E.; Baroni, P.; Petit, S.; Szuszkiewicz, W. (Видавництво Львівської політехніки, 2012)
In order to investigate the temperature dependence of the ZnO phonon dispersion the inelastic neutron scattering measurements were performed on large, single crystal of this compound. The acoustic branches were determined at several temperatures between liquid helium temperature and room temperature along selected highsymmetry directions in the Brillouin zone.
Keywords: inelastic neutron scattering; acoustic phonon dispersion; ZnO